Analisis Peranan Penerimaan Retribusi Pariwisata Terhadap Peningkatan Pendapatan Asli Daerah Kabupaten Tanah Laut Tahun 2013-2017 - Annisa; Rizali (PPJP ULM, 2019)
The purpose of the research is (1) to find out the role of tourism retribution toRegional Retribution and Original Local Government Income(PAD) in Tanah Laut Districtduring the 2013-2017 fiscal year, (2) to know the retribution collection level of effectivenessin Tanah Laut District during 2013-2017 fiscal year, (3) to see the impact of of the tourismdevelopment after the result of tourism retribution in Tanah Laut district during 2013-2017fiscal year, (4) analyze the efforts that must be made by the government of Tanah LautDistrict on developing tourism objects as one of the sources of Original Local GovernmentIncome(PAD.The research method used quantitative descriptive analysis using secondary andprimary data, through the collection and available data on the Department of Culture andTourism of Tanah Laut District and related agencies, and also the literature that has to dowith this research besides conducting interviews or interviews directly with relevantagencies, administrator, and tourist in Tanah Laut District.The results showed that the average role tourism retribution in Tanah Laut Districtduring the 2013-2017 fiscal year was very lacking, which is 5,97% for the intermediate roleof the tourism retribution on regional retribution, and 0,27% for the role average tourismretribution on Original Local Government Income (PAD). The calculation of the effectivenesslevel of tourism retribution in Tanah Laut District showed less effective results with anaverage of 78,75%.The receipt of tourism retribution in Tanah Laut District has an impact on thedevelopment of the tourism objects itself, especially tourism objects that have contributed toretribution Incomes such as Takisung Beach, Batakan Beach, Swarangan Beach, Batu LimaBeach, Sepeda Air, Kereta Wisata, Tirta Kirana Swimming Pool, Kayangan Mountain, andBajuin Waterfall.The efforts that must be made by the Tanah Laut Government, especially the TanahLaut Department of Culture and Tourism, to develop the tourism sector are organizingattractive tourism events, allocating sufficient funds for the development and managementcosts of the tourism sector, improving the main facilities and infrastructure in tourism objectplaces, improve human resources especially for the administrator of tourist attractions,socialization to the public and agencies/institutions to support the success of tourism sector,and intensify the promotion of tourism objects.